MANUSIA DAN GEGURITAN DI SURABAYA (Kajian Semiotik Disertai Telaah Subkultur) - Joko Susilo; Niko Fediyanto (Institut Teknologi Sepuluh Nopember, 2017)
The movement of geguritan (javanese poem) is not just a resistancemovement towards the general rule of Javanese literature. It providesconvenience for the community (in the same subculture) to understandJavanese culture easier. This movement refers to the 'whole way of life' or'maps of meaning' that makes this world understandable by its members.The word 'sub' connotes a specific, unique condition and different than thedominant society. Person who was born in arekan environmentor Suroboyoan often encounter difficulties when trying to comprehendMataraman Javanese. Geguritan is a manifestation of the ideas or creativitygenerated by penggurit (poet). In Surabaya, a group of geguritan authors isone subculture, that offers a new view, reinterpret the old view, andsometimes even break a single truth that have been taught long enough toJavanese community in Surabaya